2005
DOI: 10.1093/nar/gki741
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of DNA quadruplexes induced by HIV-1 nucleocapsid protein

Abstract: The human immunodeficiency virus type 1 nucleocapsid protein (NC) is a nucleic acid chaperone that catalyzes the rearrangement of nucleic acids into their thermodynamically most stable structures. In the present study, a combination of optical and thermodynamic techniques were used to characterize the influence of NC on the secondary structure, thermal stability and energetics of monomolecular DNA quadruplexes formed by the sequence d(GGTTGGTGTGGTTGG) in the presence of K+ or Sr2+. Circular dichroism studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 57 publications
5
46
0
Order By: Relevance
“…2C) (15, 27-29). It appears that NC, as reported previously in several other studies, has distinct effects on different forms of G-quartets (43,44). Specifically, the results suggested that NC stabilized the G-quartet dimer but destabilized the G-quartet monomer.…”
Section: Effects Of Nc On G-quartet-related Pauses During Strandsupporting
confidence: 79%
See 2 more Smart Citations
“…2C) (15, 27-29). It appears that NC, as reported previously in several other studies, has distinct effects on different forms of G-quartets (43,44). Specifically, the results suggested that NC stabilized the G-quartet dimer but destabilized the G-quartet monomer.…”
Section: Effects Of Nc On G-quartet-related Pauses During Strandsupporting
confidence: 79%
“…Interestingly, an apparent divergence of the influence of NC on distinct forms of G-quartets was observed recently. A circular dichroism study demonstrated that NC destabilized DNA monomer quadruplexes formed by the sequence d(GGT TGG TGT GGT TGG) in the presence of K ϩ or Sr 2ϩ , presumably through the unstacking of the G-quartets upon protein binding (43). Significantly, this G-quartet monomer destabilization activity of NC relies on its zinc finger domain but not its basic domain because EDTA-treated NC failed to influence G-quartet folding, whereas truncated NC (11-55) lacking the N-terminal basic domain still maintained the G-quartet destabilization activity (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water-soluble meso-tetra(4-N-oxyethylpyridil) porpyrin (TOEPyP4) and its Zn-containing analogue was synthesized in ESU according to the method described in work [18], and it was kindly granted by professor S. , where M w is molecular weight, and ε 422 and ε 440 are Sore absorption bands initiated by binding of porphyrin to DNA. All studies were carried out in buffer solution 10 mM NaCl, 1 mM Na-phosphate, and Ph 7.02.…”
Section: Methodsmentioning
confidence: 99%
“…Besides this, CD spectra of semustine-DNA complexes illustrate isoelliptic behavior at 231 and 258 nm (isosbestic points shown by red circles in Figure 8). This can be ascribed to semustine induced two-state transition in DNA molecule (Mayer & Drago, 1976;Kankia, Barany, & Musier-Forsyth, 2005), as semustine exerts its anti-cancer mechanism of action in two phase (formation of O6-chloroethyl guanine adducts pursued by the development of dG-dC DNA cross-links). Further, this is in corroboration with the FTIR spectral outcomes that signify an initial interaction of semustine with thymine followed by the formation of dG-dC DNA cross-links.…”
Section: Spectroscopic Analysismentioning
confidence: 99%